2021
DOI: 10.1093/jac/dkab072
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antiviral activity of the anti-HCV drugs daclatasvir and sofosbuvir against SARS-CoV-2, the aetiological agent of COVID-19

Abstract: Background Current approaches of drug repurposing against COVID-19 have not proven overwhelmingly successful and the SARS-CoV-2 pandemic continues to cause major global mortality. SARS-CoV-2 nsp12, its RNA polymerase, shares homology in the nucleotide uptake channel with the HCV orthologue enzyme NS5B. Besides, HCV enzyme NS5A has pleiotropic activities, such as RNA binding, that are shared with various SARS-CoV-2 proteins. Thus, anti-HCV NS5B and NS5A inhibitors, like sofosbuvir and daclatas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(61 citation statements)
references
References 33 publications
3
57
0
1
Order By: Relevance
“…Besides remdesivir, several other clinically approved nucleoside analogue compounds are currently under study for treating COVID-19 [11]. Molnupiravir [12,13] and AT-527 [14] are the most promising candidates so far, while ritonavir [15], ribavirin [16], favipiravir [17] and sofosbuvir [6,18] have not demonstrated significant antiviral effect against SARS-CoV-2 in the laboratory or clinical settings.…”
Section: Introductionmentioning
confidence: 99%
“…Besides remdesivir, several other clinically approved nucleoside analogue compounds are currently under study for treating COVID-19 [11]. Molnupiravir [12,13] and AT-527 [14] are the most promising candidates so far, while ritonavir [15], ribavirin [16], favipiravir [17] and sofosbuvir [6,18] have not demonstrated significant antiviral effect against SARS-CoV-2 in the laboratory or clinical settings.…”
Section: Introductionmentioning
confidence: 99%
“…We previously demonstrated that the FDA approved HCV NS5A inhibitors, Daclatasvir and Velpatasvir, and to a lesser extent the NS5A inhibitors Elbasvir and Ledipasvir, can inhibit the SARS-CoV-2 exonuclease 29 . Of particular interest, Daclatasvir and Velpatasvir inhibit both the SARS-CoV-2 polymerase and exonuclease 20,21 . Here, we showed that two additional NS5A inhibitors, Pibrentasvir and Ombitasvir, also inhibit the exonuclease, and have the highest inhibitory activity based on our molecular assay.…”
Section: Discussionmentioning
confidence: 99%
“…The RdRp of SARS-CoV-2, referred to as nsp12, and its two protein cofactors, nsp7 and nsp8, shown to be required for the processive polymerase activity of nsp12, were cloned and purified as described 11,20…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations